Photochromic properties of thienylpyrrole azo dyes in solution - Coelho, Paulo J. (2006)
The photochromic behaviour of thienylpyrrole azo dyes in THF solutions was studied for the first time. The photochromic properties are strongly dependent on the substitution pattern on the dyes. Nitro-substituted thienylpyrrole azo dyes are particularly interesting since they exhibit very fast colouration/decolouration processes. The activation energies of these compounds are among the lowest values reported for heterocyclic azo dyes. These compounds show aggregation phenomena in freshly prepared solutions of THF, which lead to variable photochromic behaviours. Only after 1–5 h the solutions reach equilibrium and then reproducible photochromic behaviour can be observed.